EFEKTIVITAS PENGGUNAAN PESAN DALAM MEDIA KOMUNIKASI PEMASARAN ONLINE - Agustina Multi Purnomo (Universitas Lambung Mangkurat, 2023)
The use of online marketing media as a marketing communication medium has proliferated. This study examined the effectiveness of used messages in online marketing communication media, websites, and Instagram, to market IndiHome products. This study used elements of the message content (clarity of message content, the relevance of message content to the product being promoted, as well as the availability of visual, textual, and audiovisual information), accuracy between messages and media characters (informative and entertaining information on Instagram, as well as single consistent information in the website media), and the effectiveness of the used of messages (customers' responses to the attractiveness of the message and the encouragement of buying interest after seeing the message). This study found elements of message content and the accuracy of messages with media characters to get a positive response from customers and potential customers. The two factors of using messages in online marketing communication media are considered attractive by customers and potential customers or effective. However, the use of messages did not directly encourage buying interest. This study proposed adding an element of distinction inherent in the product that cannot be overcome by using messages in online marketing communication.